Relevance of Legal Capacity as Legitimate Terms of Agreement of Saving for Child in the Bank - Ari, Muhammad As; Imanullah, Moch Nadjib; Setiono, Setiono (The Indonesian Journal of International Clinical Legal Education, 2019)
Indonesia is law state such as inserted in constitutional 1945.Legitimation Indonesia as law state have the impact that all attitudehave to relevance by law. Similarly act such as saving in the bank. Thelaw Number 10 year 1998 concerning change of the law Number 7 year1992 concerning the banking stated the definition account saving asfollows: Ã¢â‚¬Å“account saving is savings who can be taken accord agreementof parties only, but it canÃ¢â‚¬â„¢t be taken with check, billyet, giro ectÃ¢â‚¬Â. Thedefinition of account saving upon explain implicitly that terms ofagreement of saving surrender parties (pay attention of sentenceÃ¢â‚¬Å“according specialist term by partiesÃ¢â‚¬Â). The sentence upon is normblanked should facilitate the child for saving independent according ofthe best interest of the child principle. But the banking decided use thegeneral law about legal capacity one forbidden the child savingindependent. The law one forbidden the child saving independent isgoing to give impact such as is blocked protective of law to interestchild are for live, grow and develop for prepare the future their selves.Salving independent by the child are growth and developmentpsychologically. According a research by Child and Youth FinanceInternational said Ã¢â‚¬Å“the human one saving since child period is betterthan the human donÃ¢â‚¬â„¢t save since child period. ItÃ¢â‚¬â„¢s mean attitude savingis going to become the child find best growth and the bestpsychological development.